Junie : a novel - Eckstine, Erin Crosby (Good morning America book club., 2025)
"A strong-willed enslaved girl is haunted by her sister's ghost as she grapples with circumstances beyond her control, risking her life as the Civil War looms in this lush and tenderhearted debut. Junie has always yearned for more. Born and raised on the Bellereine plantation in the Alabama countryside, the sixteen-year-old spends her days working for the McQueens and serving as a maid for their daughter Violet, her oldest and closest friend. In the daytime, she entertains herself with poetry and imagines grand romances and faraway worlds. Under the cover of night, she steals away to the woods, curling up by the riverbank. But consumed by grief over the recent death of her older sister Minnie, she has vowed never to leave her family's side. Her world is capsized at the arrival of the Taylors, a wealthy brother and sister from New Orleans. The McQueens are keen to marry Violet off to Mr. Taylor, and if they succeed, Junie would be ripped away from everyone she knows and loves. Committing a desperate act, she awakens Minnie's tempestuous spirit, who can only move on once Junie completes three crucial tasks. She enlists the aid of Caleb, Mr. Taylor's chauffeur, and the two strike up a quick friendship that soon becomes something more. Yet time is ticking, and as secrets and betrayals rise to the surface, Junie must wade into unfamiliar territory as she pushes against the current that has controlled her entire life. Encapsulating the multitudes of a young girl caught between the steadiness of the familiar and the gamble of diving into the unknown, Erin Crosby Eckstine explores the strength of love and friendship under the crushing weight of servitude. In this radiant and stirring novel, Junie soars to life, brimming with longing that cannot be contained and hope that can never be extinguished"--